ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT PENGANGGURAN TERBUKA DI PROVINSI BANTEN 2018-2022 - Miftahul Annam, Muhammad; Safar Nasir, Muhammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research is entitled analysis of factors affecting the open unemployment rate in Banten Province 2018-2022. The purpose of this study is to see how the influence of HDI, Total Population, Labour Force & Minimum Wage on the Open Unemployment Rate in 8 Regency / City in Banten Province in 2018-2022. In this study, panel data analysis method and STATA were used as analytical tools. The results showed that simultaneously the variables of Minimum Wage, Population, Human Development Index, Labour Force, had an influence on the Open Unemployment Rate in Banten Province. The percentage variable of HDI has a negative and significant effect on the open unemployment rate, the minimum wage variable has a positive and significant effect on the open unemployment rate, while the population and labour force variables have no effect on the open unemployment rate. In accordance with the results of this study.